Analysis of Motility Characteristic of Pesisir Bulls Sexed Semen with Different Pre-Freezing Method Based on Computer Assisted Sperm Analyzer (CASA) - Dwiki Wahyudi; Zaituni Udin; Tinda Afriani (Faculty of Animal Science, Universitas Gadjah Mada, 2023)
This study aimed to find the best combination between pre-freezing method and layer of post sexing on semen quality of Pesisir Bulls. This study used 2 Pesisir Bulls. The semen was evaluated using Computer Assisted Sperm Analyzer (CASA). This study used factorial randomized block design with 2 factors. Factor A was sexed semen layer of BSA column with 2 level, whereas Factor B was pre-freezing method with 3 level. Analysis of Variance (ANOVA) were used in this study for data Analysis. According to the analysis of variance, there is no interaction of the combination of two factors on each paramters. Pre-freezing method showed highly statistically significant effect (P<0.01) on the quality of motility on upper layer and bottom layer which was about (52.86-72.93%; 52.32-65.50%) and about (40.17-56.99%; 40.33-53.18%) on progressive motility. The value of Distance Curve Line on (39.15-43.24 μm; 49.25-53.86 μm), Distance Average Path (22.38-24.60 μm; 26.52-29.94 μm), Distance Straight Line (17.32-19.07 μm; 20.93-24.25 μm). The value of Velocity Curve Line (88.67- 97.50 μm/s; 109.85-117.90 μm/s), Velocity Average Path (50.98- 55.63 μm/s; 59.32- 64.69μm/s), Velocity Straight Line (34.45-42.37 μm/s; 46.80-50.62 μm/s), Beat Cross Frequancy (23.91-25.17 Hz; 25.63-27.35 Hz), Straightness (0.75-0.77; 0.77-0.80), and Wobble (0.56-0.57; 0.53-0.55), highly statistically significant (P<0.01) on post sexing layers. Meanwhile, the value of Amplitude of Lateral Head (4.24-4.94 μm; 4.25-4.44 μm) showed highly significant effect (P<0.01) on factor A and factor B treatment, and value Linearity was about (0.42-0.44; 0.43-0.44) showed not significant effect (P>0,05) on every factor. According to the study, it can be concluded that the best treatment was treatment modified procedure layer by space the straw 16 cm every layers and The quality of post sexing X- and Y- spermatozoa motility effect on motility characteristic such as DCL, DAP, DSL, VCL, VAP, VSL, STR, WOB, ALH and BCF.